The export promoting effect of emigration: Evidence from Denmark - Sanne Hiller (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2011)
The theoretical claim that ethnic networks encourage trade has found broad empirical support in the literature on migration, business networks and international trade. Ethnic networks matter for the exporting firm, as they exhibit the potential to lower fixed and variable cost of exporting. This paper provides a first attempt to identify the export-promoting effect of emigration on the firm level. Using detailed Danish firm-level data, we can parsimoniously control for export determinants other than emigration, unobserved heterogeneity at the firm level, as well as for self-selection of firms into exporting. Additionally accounting for taste similarity between Denmark and its trade partners, our findings suggest a positive effect of emigration on Danish manufacturing trade within Europe, thereby corroborating preceding studies on aggregate data. Nevertheless, as a novel insight, our analysis reveals that the only beneficiaries of emigration are small enterprises.
Keywords: F22; F16; 330; Emigration; Brain Drain; Small Businesses; International Trade; Firm-level analysis; Internationale Wanderung; Brain Drain; KMU; Außenhandel; Dänemark